Making the Most of Mess Reliability and Policy in Today's Management Challenges - Roe, Emery (Duke University Press, 2013)
In Making the Most of Mess, Emery Roe emphasizes that policy messes cannot be avoided or cleaned up; they need to be managed. He shows how policymakers and other professionals can learn these necessary skills from control operators who manage large critical infrastructures such as water supplies, telecommunications systems, and electricity grids. The ways in which they prevent major accidents and failures offer models for policymakers and other professionals to manage the messes they face. Throughout, Roe focuses on the global financial mess of 2008 and its ongoing aftermath, showing how mismanagement has allowed it to morph into other national and international messes. More effective management is still possible for this and many other policy messes but that requires better recognition of patterns and formulation of scenarios, as well as the ability to translate pattern and scenario into reliability.